Convulsive Tic Disorder Georges Gilles de la Tourette, Guinon and Grasset on the Phenomenology and Psychopathology of Gilles de la Tourette Syndrome - Mary M. Robertson; Dan Z. Reinstein (Behavioural Neurology)
Gilles de la Tourette gained eponymous fame when he described nine cases of multiple tics, coprolalia and echolalia, and later he, Guinon and Grasset were the first to document the psychopathology of the Gilles de la Tourette syndrome. In particular, they noted the association between obsessional thoughts and behaviours and the tic disorder. In this paper we present the first English translations of their works referring to the psychopathology, comparing and contrasting their ideas to current concepts.